KOMUNIKASI AIDA - SEBUAH STRATEGI PENDAMPINGAN PSIKOSOSIAL DAN PENGUATAN IMPLEMENTASI PEMBELAJARAN SEKOLAH DASAR DI KABUPATEN BANGKA BARAT - Gustin, Gustin; Septiadi, Septiadi (MEDIOVA: Journal of Islamic Media Studies, 2024)
Communication fatigue, limited interpersonal communication, spatial and temporal limitations in learning activities, and decreased student confidence are issues that need to be addressed. This research uses a descriptive qualitative method. Data were collected through interviews, observations, and documentation, and the findings were analyzed using Mills & Hubberman's qualitative analysis. Based on the results and discussions related to AIDA Communication - A Strategy for Psychosocial Assistance and Strengthening the Implementation of Elementary School Learning in West Bangka Regency, it is concluded that the first stage, Attention, involves analyzing and identifying the issues faced by elementary schools to provide psychosocial assistance and strengthen the implementation of learning. The second stage, Interest, includes a needs analysis that generates interest in the psychosocial assistance and learning implementation strengthening program for schools. The third stage, Desire, involves preparing teaching videos and supervising classroom teaching. The fourth stage, Action, involves sustainable program actions that can be independently implemented by schools, ensuring the sustainability of the school's culture and its impact.